An anti-unwinding finite time fault tolerant sliding mode control of a satellite based on accurate estimation of inertia moments. (June 2020) - Shahna, Mehdi Heydari; Abedi, Mostafa
Abstract: Design of an adaptive anti-unwinding finite time sliding mode algorithm for attitude control system of a three-axis satellite is approached in this paper. In the designed controller, some parameters updating laws are proposed to simultaneously obtain the accurate values of inertia moments, the upper values of reaction wheels' failures and disturbances. Accordingly, the combined finite time stability of the control system and convergence of the satellite parameters has been demonstrated. Also, a new sliding surface is suggested to avoid the unwinding problem which is common in sliding mode techniques. It is proved by the Lyaponov methodology that the satellite quaternions and angular velocities always approach to the nearest equilibrium point and so it prevents the excessive satellite slews. Furthermore, the proposed algorithm has been modified in such a way that the singularity problem does not occur, especially when the system states reach around the equilibrium point. Therefore, the finite time convergence of system states and parameters estimation errors are guaranteed subjected to disturbances and actuator failures without occurring singularity and unwinding problems. Besides rigorous theoretical proofs by the Lyapunov theory, different simulations are exhibited to demonstrate the merits of the developed control schemes. Highlights: An adaptive finite time sliding mode control is proposed for a rigid satellite. The finite time stability is ensured despite accurate estimation of parameters. The upper bound of disturbances and actuator failures are estimated. The unwinding and singularity problems are prevented. It is concluded that the suggested controller has superior accuracy and chattering.